Revalidation of the genus Sadala Simon, 1880 with the description of a new genus of Neotropical huntsman spiders (Araneae, Sparassidae) - Rheims, Cristina A.; Jäger, Peter (Zootaxa, 2022)
The genus Sadala Simon, 1880 is revalidated to include the here designated type species, S. keyserlingi Simon, 1880, as well as S. nigristernis Simon, 1880, S. punicea Simon, 1880, S. rufa (Keyserling, 1880) and S. velox Simon, 1880, all comb. rest. The males of S. punicea and S. rufa and four new species are described: S. kaiabi spec. nov. (♂♀), from Brazil, S. nanay spec. nov. (♀) and S. yuyapichis spec. nov. (♂) from Peru, and S. tabatinga spec. nov. (♀) from Brazil and Colombia. The genus Meri gen. nov. is described to include the type species, M. pictitarsis (Simon, 1880), as well as M. mathani (Simon, 1880), M. formosus (Banks, 1929), M. santivincenti (Simon, 1898), and M. trinitatis (Strand, 1916), all comb. nov. transferred here from the genus Olios Walckenaer, 1837. The male of M. trinitatis comb. nov. and twenty new species are described: M. abuna spec. nov. (♂♀), from Ecuador, Brazil and Peru; M. aparia spec. nov. (♀), from Peru, M. arraijan spec. nov. (♀) from Panama and Colombia; M. carabobo spec. nov. (♂♀), M. guri spec. nov. (♂), M. yaciba spec. nov. (♂♀), from Venezuela; M. conduri spec. nov. (♂♀), M. manaos spec. nov. (♂), M. munduruku spec. nov. (♀), M. paiaia spec. nov. (♀), M. quinari spec. nov. (♂), M. rivai spec. nov. (♀), M. tambor spec. nov. (♂), M. tapirapeco spec. nov. (♀), from Brazil; M. jaraua spec. nov. (♂♀), from Venezuela, French Guiana, Surinam, Ecuador, Peru and Brazil; M. kaieteur spec. nov. (♀) from Venezuela and Guyana; M. martinique spec. nov. (♀), from Martinique, Guadelupe and Dominica; M. tumatumari spec. nov. (♀) from Guyana, M. vanini spec. nov. from Brazil and Peru; and M. zeteki spec. nov. (♀) from Panama. Olios orchiticus Mello-Leitão, 1930 is considered a junior synonym of M. trinitatis comb. nov. Both genera and species are described and illustrated. Identification keys and updated distribution maps are provided.